Vena cava thrombus in patients with wilms tumor - Meier, Clemens-Magnus; Furtwängler, Rhoikos; Schweinitz, Dietrich von; Stein, Raimund; Welter, Nils; Wagenpfeil, Stefan; Kager, Leo; Schenk, Jens-Peter; Vokuhl, Christian Oliver; Melchior, Patrick; Fuchs, Jörg; Graf, Norbert (Cancers, 2022)
(1) Background: Vena cava thrombus (VCT) is rare in Wilms tumor (WT) (4-10%). The aim of this study is to identify factors for an outcome to improve treatment for better survival. (2) Methods: 148/3015 patients with WT (aged < 18 years) and VCT, prospectively enrolled over a period of 32 years (1989-2020) by the German Society for Pediatric Oncology and Hematology (SIOP-9/GPOH, SIOP-93-01/GPOH and SIOP-2001/GPOH), are retrospectively analyzed to describe clinical features, response to preoperative chemotherapy (PC) (142 patients) and surgical interventions and to evaluate risk factors for overall survival (OS). (3) Results: 14 VCT regressed completely with PC and another 12 in parts. The thrombus was completely removed in 111 (85.4%), incompletely in 16 (12.3%), and not removed in 3 (2.3%). The type of removal is unknown in four patients. Patients without VCT have a significantly (p < 0.001) better OS (97.8%) than those with VCT (90.1%). OS after complete resection is (89.9%), after incomplete (93.8%) and with no resection (100%). Patients with anaplasia or stage IV without complete remission (CR) after PC had a significantly worse OS compared to the remaining patients with VCT (77.1% vs. 94.4%; p = 0.002). (4) Conclusions: As a result of our study, two risk factors for poor outcomes in WT patients with VCT emerge: diffuse anaplasia and metastatic disease, especially those with non-CR after PC.
Der Artikel ist Teil des Special Issue: New insights in pediatric surgical oncology
Gesehen am 15.09.2022